2020
DOI: 10.3390/pathogens9020120
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Network of Interactions in the Wildlife-Livestock Interface in Mediterranean Spain: An Epidemiological Point of View

Abstract: The correct management of diseases that are transmitted between wildlife and livestock requires a reliable estimate of the pathogen transmission rate. The calculation of this parameter is a challenge for epidemiologists, since transmission can occur through multiple pathways. The social network analysis is a widely used tool in epidemiology due to its capacity to identify individuals and communities with relevant roles for pathogen transmission. In the present work, we studied the dynamic network of interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(51 citation statements)
references
References 50 publications
1
50
0
Order By: Relevance
“…Interestingly, we found a significant association between the presence of TBL in cattle and the prevalence of TBL in fallow deer (see Figure 6 ). Previous studies on spatiotemporal interaction patterns among wild ungulates and cattle carried out in DNP showed that the dynamics of TB transmission in this area is conditioned by environmental and habitat-related peculiarities which facilitate the spatiotemporal direct and indirect overlap between wildlife and livestock species [ 25 , 29 , 30 ] ( Figure 10 ). Interestingly, high contact rates between fallow deer and cattle have been reported in DNP [ 13 , 30 ].…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…Interestingly, we found a significant association between the presence of TBL in cattle and the prevalence of TBL in fallow deer (see Figure 6 ). Previous studies on spatiotemporal interaction patterns among wild ungulates and cattle carried out in DNP showed that the dynamics of TB transmission in this area is conditioned by environmental and habitat-related peculiarities which facilitate the spatiotemporal direct and indirect overlap between wildlife and livestock species [ 25 , 29 , 30 ] ( Figure 10 ). Interestingly, high contact rates between fallow deer and cattle have been reported in DNP [ 13 , 30 ].…”
Section: Discussionmentioning
confidence: 98%
“…However, we cannot ignore differences in exposure in a grazing species that mainly use open areas, in contrast to the more habitat generalist wild boar and red deer. In DNP, intra and interspecific contact networks, and the subsequent molecular epidemiology pattern (distribution of the M. bovis types), seems to act at a very local scale at the host community level [ 19 , 25 , 30 ]. Previous studies on molecular epidemiology of TB in DNP have suggested that a local transmission frequently occurs between species [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations